Negotiating justice the struggle of selected families of victims of media killings - Ragragio, Jefferson Lyndon Dagsindal (Quezon City Department of Communication Research, College of Mass Communication, University of the Philippines Diliman, 2014)
This study inquires into the negotiation process that the families of slain media workers in the Ampatuan-Maguindanao massacre and other media killing cases nationwide undergo in their clamour for justice and assistance from key stakeholders in the media rights, civil society and government organizations. Using Williams' Cultural Studies, this study explores the interplay among power, politics and culture in the context of negotiation.Considering the wide spectrum of process involved in negotiation, this study further determines the actual roles performed by the government and non-government organizations and their impact on the struggle for justice of the families.Qualitative research methods consisting of focus individual and groupinterviews and participant observation were utilized to comprehensively analyze the flow of negotiation between the families and organizations. The families, as the focus of this study, employ certain negotiation styles to communicate their need for assistance including (1) Dependency, (2) Right-to-Demand, (3) Adversarial, (4) Participative, (5) Political-Relational, and (Submissive-Silent styles. They exert cultural practices to sustain their call for justice through mass commemorations and public campaigns.
"April 2014."
Thesis (M.A. Communication)--University of the Philippines Diliman.
Keywords: Murder victims in mass media